PENGUJIAN BERAS AKING SEBAGAI BAHAN MAKANAN - Bambang N.; Heri R. M.; Tita R.; Suryana Purawisastra (Persagi, 2008)
The Study On The Used Rice as Staple Food.Background: Due to the high price of rice, some people used the used rice known as